2020
DOI: 10.1111/pan.13953
|View full text |Cite
|
Sign up to set email alerts
|

Use of a simulation‐based mastery learning curriculum to improve ultrasound‐guided vascular access skills of pediatric anesthesiologists

Abstract: Background: Pediatric vascular access is inherently challenging due to the small caliber of children's vessels. Ultrasound-guided intravenous catheter insertion has been shown to increase success rates and decrease time to cannulation in patients with difficult intravenous access. Although proficiency in ultrasound-guided intravenous catheter insertion is a critical skill in pediatric anesthesia, there are no published competency-based training curricula. Aims: The objective of this study was to evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…We obtained study approval from the Lurie's Children's Hospital Institutional Review Board (IRB 2019–2860, approved 6/10/19, chairperson Jennifer Rubin), and the requirement for written informed consent was waived by the IRB. IRB approval was initially obtained for another prospective study evaluating IV insertion outcomes after an educational intervention 23 …”
Section: Methodsmentioning
confidence: 99%
“…We obtained study approval from the Lurie's Children's Hospital Institutional Review Board (IRB 2019–2860, approved 6/10/19, chairperson Jennifer Rubin), and the requirement for written informed consent was waived by the IRB. IRB approval was initially obtained for another prospective study evaluating IV insertion outcomes after an educational intervention 23 …”
Section: Methodsmentioning
confidence: 99%
“…Our curriculum in ultrasound-guided intravenous catheter insertion in pediatric patients showed that only 21% of attendings, fellows, or residents were able to meet a minimum passing score on a pretest checklist. 2 Fortunately, all of our participants were able to meet this standard after participation in the curriculum and also reported improved self-confidence with this skill. Fatima et al’s 1 study echoes previous literature that has shown that procedural experience does not ensure competence in trainees.…”
Section: To the Editormentioning
confidence: 75%
“…When designing our module, we primarily used the simulation-based procedural training (SBPT) method as it had already shown efficacy in teaching ultrasound-guided procedures. 22 SBPT allows learners to gain procedural skills in a controlled, low-stakes, standardized, and supervised learning environment that can be designed to accommodate learners' specific needs and assess their skills against standards of achievement. 23 SBPT is now widely used in medical education in lieu of the traditional “see one, do one, teach one” apprentice model as it reduces harm to patients and has been associated with acquisition of procedural competency by learners.…”
Section: Introductionmentioning
confidence: 99%